Handbook of educational psychology - Schutz, Paul A.; Muis, Krista R. (New York: Routledge, 2024)
"The fourth edition of the Handbook of Educational Psychology, sponsored by Division 15 of the American Psychological Association, addresses new developments in educational psychology theory and research methods while honoring the legacy of the field's past. Comprised of thirty-one chapters written by a diverse group of recognized Educational Psychologist and/or Learning and Motivational Scientist (EDP/LMS) scholars, this volume provides integrative reviews and critical syntheses of inquiry across a variety of foundational and new areas. Key constructs like motivation, development, beliefs, literacy, and emotions are given substantive updates, while entire new chapters in touch on trends that have materialized since the publication of the third edition, such as inquiry world views, Critical Race Theory, cognitive neuroscience, and emerging technologies in education. Throughout this new edition, chapter authors coalesce on issues of social justice, situated approaches to inquiry, and progressive inquiry methods. The Handbook of Educational Psychology, Fourth Edition, will be an important reference volume for current and future EDP/LMS scholars, broadly conceived, as well as for teacher educators, practicing teachers, policy makers and the academic libraries serving these audiences. It is also appropriate for graduate-level courses in educational psychology, learning and motivational sciences, and research methods in education and psychology"--
Second edition edited by Patricia Alexander and Philip Winne. Third edition edited by Lyn Corno and Eric M. Anderman.
Includes bibliographical references and index.
Keywords: Educational psychology -- Handbooks, manuals, etc